Testosterone and FSH modulate Sertoli cell extracellular secretion: Proteomic analysis. (15th November 2018) - Mancuso, Francesca; Calvitti, Mario; Milardi, Domenico; Grande, Giuseppe; Falabella, Giulia; Arato, Iva; Giovagnoli, Stefano; Vincenzoni, Federica; Mancini, Francesca; Nastruzzi, Claudio; Bodo, Maria; Baroni, Tiziano; et al.
Abstract: Spermatogenesis is a highly complicated biological process that occurs in the epithelium of the seminiferous tubules. It is regulated by a complex network of endocrine and paracrine factors and by juxtacrine testicular cross-talk. Sertoli cells (SC) play a key role in spermatogenesis due to their production of trophic, differentiation and immune-modulating factors, but many of the molecular pathways of SC action remain controversial and unclear. Over the last two decades, research has focused on extracellular vesicles as an important mechanism of intercellular communication. The aim of this study was to investigate the presence of extracellular vesicles (EVs) in SC and the modulation of their content in SC after FSH and testosterone stimulation. Highly purified porcine pre-pubertal Sertoli cells were isolated according to previously established methods. After 48 h of culture with FSH or FSH + testosterone stimulation, we identified sertolian EVs containing specific mRNAs. Proteomic analysis of EVs content identified 29 proteins under non-stimulatory conditions, most of which were related to receptor binding activity. FSH stimulation induced increases in inhibin-alpha, inhibin-beta, plakoglobin, haptoglobin, D-3-phosphoglycerate dehydrogenase and sodium/potassium-transporting ATPase in sertolian EVs. Testosterone stimulation enhanced the abundance of inhibin-alpha, inhibin-beta, tissue-type plasminogen activator, epidermal growth factor-like protein 8, elongating factor 1-gamma and D-3-phosphoglycerate dehydrogenase. These results are likely to help determine the unknown molecular secretion of Sertoli cells.